Biochemical and molecular evaluation of neutrophil NOS in spontaneously hypertensive rats - Chatterjee, M.; Saluja, R.; Kanneganti, S.; Chinta, S.; Dikshit, M. (Cellular and Molecular Biology, 2007)
Resting neutrophils generate NO, while activation leads to the production of reactive oxygen and nitrogen species. Nowadays cardiovascular pathological conditions such as hypertension, cardiac ischemia, reperfusion and heart failure are associated with inflammation. This project explores the respiratory burst potential and NO generation status in the neutrophils, plasma, aorta, and kidneys from normotensive Wistar and spontaneously hypertensive rats (SHR). Total and protein associated nitrite content was quantitated using Griess reagent following cadmium reduction and mercuric chloride treatment respectively. NO and superoxide generation evaluated by Flowcytometry and peroxynitrite by spectrofluorimetric method. Expression of NOS isoforms was analyzed by RT-PCR. NO generation from SHR neutrophils was significantly augmented in comparison to normotensive counterparts. Neutrophils activated in response to arachidonic acid, PMA, fMLP or E. coli generated more superoxide radicals among SHR, and consequentially peroxynitrite. Expression of iNOS was significantly more in the SHR neutrophils, while that of nNOS remained unaffected. Results suggest that NO generated in SHR is utilized in scavenging superoxide radicals thereby limiting its bioavailability. Thus induction of NOS in neutrophils combined with augmented oxidative stress might influence its association with endothelium and contribute to inflammatory responses under hypertensive condition.